Racionalidade formal e racionalidade substantiva em organizações de extensão rural: um estudo com os tipos organizacionais burocrático e coletivista - Rossés, Gustavo Fontinelli (2015)
At the end of the twentieth century has seen great concern with issues surrounding where, how, why and how the technical assistance and rural extension has consolidated its fundamental importance as a promoter of access to new technologies and diverse knowledge. In this scenario, the emerging technical assistance and rural extension, which initially relied on priority government actions. Faced with a lack of a political scenario to coordinate the Ater the national level, Brazil has generated a pluralistic extension system, very similar to molds that are now recommended by international experts. Numerous discussions and nominations emerged in order to give greater meaning and understanding to the subject so vast and nebulous that comes up, such as organizational contingencies, the type of organizational rationality and the implications for the extension action. Based on these considerations, attention-grabbing two particular cases, leading to research on how rationality formal and substantive can impact on organizational activities in the field of agricultural extension. These cases are CETAP Technology Center Alternative and Popular and EMATER Rio-Grandense Association of Technical Assistance and Rural Extension Projects. Thus, this thesis aimed to analyzing the organizational and environmental contingencies on the rationality employed in agricultural extension organizations, and the effects on the extension action . In terms of methodology this study was characterized as qualitative. Based on a case study, this study drew on data collection through interviews, questionnaires, document analysis and direct observation, being designed from a detailed set of analytical categories. In terms of analysis of the results were adopted the classification techniques, categorization and essentially content analysis. The results showed that the CETAP operates so predominant within a logic of substantive rationality, while EMATER operates primarily based on the assumptions of a formal rationality. It was also possible to conclude that public políticas technical assistance and rural extension have considerably influenced the comportamaneto these organizations, with lower intensity in the case of CETAP and with greater intensity to EMATER. Finally, it was also established that the public políticas and organizational rationality has influenced directly, both CETAP as in EMATER, how extensionsitas practices have been developed, both from the point of view of its design, as its implementation. Keywords: Public policy. Rationality. Organizations collectives and bureaucratic. Organizations extension. Action extension